The performance of financial and monetary policy in the triple crisis (political, health and economic) in the Iraqi economy - Nagham Hameed Abdulkhudhur; Hussein Shnawa Majeed (Genius Journals, 2023)
The imbalance in the structure of the Iraqi economy widens with the continuation of the global price decline shocks of crude oil. In addition, to the government’s inability to find financing alternatives that support the general budget in conjunction with the health and political crisis Covid 19, so that the economy witnesses a complex economic crisis that differs from its predecessors, as the environment of the Iraqi economy has become one of the most affected rentier countries. Financial and economic shocks, due to its loss of the ability to face crises and manage them in light of the limited and low financial space needed to overcome this type of sudden crisis and the inefficient performance of monetary policy variables. As the economy has surpassed the stage of the single crisis associated with global oil prices only, to move to a new type of crisis, namely the double crises and the triple compound crisis, which resulted in a package of deep problems and imbalances, which necessitate the initiation of financial and monetary reforms that require appropriate time periods for their results to appear in a way that changes the course. The current year towards stability and then growth in the right direction
Keywords: financial; monetary; triple crisis